Photophysical Properties of Intramolecular Charge Transfer in a Tribranched Donor–π–Acceptor Chromophore. Issue 11 (28th May 2015) - Hu, Jiangpu; Li, Yang; Zhu, Huaning; Qiu, Shuhai; He, Guiying; Zhu, Xiaozhang; Xia, Andong
Abstract The photophysical properties of intramolecular charge transfer (ICT) in a novel tribranched donor–π–acceptor chromophore, triphenoxazine‐2, 4, 6‐triphenyl‐1, 3, 5‐triazine (tri‐PXZ‐TRZ), with thermally activated delayed fluorescence character was investigated in different aprotic solvents by steady‐state spectroscopy and femtosecond and nanosecond transient absorption spectroscopy measurements. Increasing the solvent polarity led to a significant increase in the Stokes shift. The large Stokes shift in highly polar solvents was attributed to ICT properties upon excitation; this resulted in a strong interaction between the tri‐PXZ‐TRZ molecule and the surrounding solvent, which led to a strong solvation process. Quantum‐chemical calculations and changes in the dipole moment showed that this compound has a large degree of ICT. Furthermore, an apolar environment helped to preserve the symmetry of tri‐PXZ‐TRZ and to enhance its emission efficiency. The femtosecond and nanosecond transient absorption spectroscopy results indicated that the excited‐state dynamics of this push–pull molecule were strongly influenced by solvent polarity through the formation of a solvent‐stabilized ICT state. The excited‐state relaxation mechanism of tri‐PXZ‐TRZ was proposed by performing target model analysis on the femtosecond transient absorption spectra. In addition, the delayed fluorescence of tri‐PXZ‐TRZ was significantly modulated by a potential competition between solvation and intersystem crossing processes.